Despite rising shares of women on executive and supervisory boards, gender parity remains a far-off goal - Virginia Sondergeld; Katharina Wrohlich; Anja Kirsch (DIW Weekly Report, 2025)
In 2024, the share of women on the top decision-making boards of the largest companies in Germany increased. A solid 19 percent of all executive board members at the 200 largest companies are now women, and almost 26 percent of members at the 40 largest listed companies are women. The financial sector is also catching up in this regard. Moreover, legal requirements, such as the inclusion requirement for listed companies with full co-determination whose executive board has at least four members, are having an effect: Nearly all companies in this group now have at least one woman on their executive board, with nearly one third even having two or more. Thus, women's access to executive board positions has improved over the past 15 years. However, this does not necessarily mean that women have the same amount of influence on the executive boards as their male counterparts. Therefore, companies must focus on developing an inclusive company culture in which diversity is reflected in both the formal composition as well as in practice.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; women directors; executive directors; gender equality; gender quota; Germany